Prediction of Energy Consumption in Buildings Using Support Vector Machine - Todorka Samardzioska*; Valentina Zileska Pancovska; Silvana Petrusheva; Blagica Sekovska (Tehnički Vjesnik, 2021)
The energy consumption of buildings can directly affect the buildings users' budget and their satisfaction with the investment in the property. Vice versa, buildings energy consumption has a social implication on the buildings' users. Additionally, building energy consumption is connected with the buildings influence on the environment due to the CO2 emission. Thus, having a model for energy usage prediction is of crucial importance. Data for sixty real-built buildings were collected. Using support vector machine, a model was developed for prediction of energy consumption. The mean absolute percentage error of the model is 2,44% and the coefficient of determination of the model R2 is 94,72%, which expresses the global fit of the model. The model is useful for all participants in the designs of buildings, particularly in the early phases. It can serve as a decision support model during the process of selection of optimal building design.